Hypertension persisting after pre-eclampsia: a prospective cohort study at Mulago Hospital, Uganda. - Annettee Nakimuli; Alison M Elliott; Pontiano Kaleebu; Ashley Moffett; Florence Mirembe (PLoS ONE)
Background Pre-eclampsia/eclampsia usually resolves after delivery but sometimes hypertension persists and cardiovascular disease develops later. Our objective was to determine the incidence and maternal socio-demographic and obstetric risk factors for persistence of hypertension in women with pre-eclampsia/eclampsia. Methods This was a prospective cohort study conducted from July 2009 to June 2011 at Mulago Hospital labour ward and postnatal clinics. We followed up 188 women admitted with pre-eclampsia/eclampsia until 3 months after delivery. Data was collected using interviewer-administered questionnaires, examination of participants and review of medical records. Stata (version12) software was used for data analysis. Univariable analysis was used to compute the relative risk of persistent hypertension at the 95% confidence level. This was followed by multivariable logistic regression analysis to determine factors independently associated with persistence of hypertension. Results 64 (34%) out of the 188 women analysed had persistent hypertension three months after delivery. Maternal age, gestational age at delivery and parity were predictors of persistent hypertension. Conclusion The proportion of women with pre-eclampsia/eclampsia at risk of persistent hypertension at three months after delivery was high, with nearly one of three mothers remaining hypertensive. Follow up of mothers who develop pre-eclampsia is important so that early diagnosis and management of chronic hypertension can be made to avoid long term morbidity and mortality.